The effect of demographic factors on behavioral biases - Vania Beatrice; Werner R. Murhadi; Arif Herlambang (Jurnal Siasat Bisnis, 2021)
The purpose of this study was to examine the influence of demographic factors such as gender, age, education, occupation, income, and investment experience on investor behavior bias such as overconfidence bias, disposition effects, herding bias, and mental accounting. This type of research was causal research with a quantitative approach, and the analytical method used was the analysis of SEM (structural equation modeling). This research was conducted by distributing questionnaires to investors listed on the Indonesia Stock Exchange with a minimum age of 17 years. The results showed that overconfidence bias was influenced by investment experience while disposition effect was influenced by age, income level, and investment experience. Herding bias was influenced by age and occupation while mental accounting was influenced by income level.